EEPD1 attenuates radiation-induced cardiac hypertrophy and apoptosis by degrading FOXO3A in cardiomyocytes - Yu Kaiwen; Su Xi; Zhou Tongfang; Cai Xuwei; Zhang Min (Acta Biochimica et Biophysica Sinica)
Radiation-induced heart disease (RIHD) is a severe delayed complication of thoracic irradiation (IR). Endonuclease/exonuclease/phosphatase family domain-containing 1 (EEPD1) plays an important role in DNA damage repair, but its role in RIHD is less known. In this study, EEPD1 global knockout mice, C57BL/6J mice, and C57BL/6J mice overexpressing EEPD1 are treated with radiation at a total dose of 20 Gy or 0 Gy. After 9 weeks, echocardiography is used to assess cardiac hypertrophy and apoptosis. The results show that EEPD1 deletion exacerbates radiation-induced cardiac hypertrophy and apoptosis, while EEPD1 overexpression has the opposite effect. Further mechanistic investigations reveal that EEPD1 interacts with FOXO3A and destabilizes it by catalyzing its deubiquitination. Inhibition of FOXO3A ameliorates cardiac hypertrophy and apoptosis after EEPD1 knockdown. Thus, EEPD1 protects against radiation-induced cardiac hypertrophy and apoptosis via destabilization of FOXO3A, which may offer new insight into therapeutic strategies for RIHD.